PI3KCA plays a major role in multiple myeloma and its inhibition with BYL719 decreases proliferation, synergizes with other therapies and overcomes stroma‐induced resistance. (9th January 2014) - Azab, Feda; Vali, Shireen; Abraham, Joseph; Potter, Nicholas; Muz, Barbara; de la, Pilar; Fiala, Mark; Paasch, Jacob; Sultana, Zeba; Tyagi, Anuj; Abbasi, Taher; Vij, Ravi; et al.
Summary The phosphatidylinositide 3‐kinase (PI3K) pathway is activated and correlated with drug resistance in multiple myeloma (MM). In the present study we investigated the role of PI3KCA (PI3K‐α) in the progression and drug resistance in MM. We showed that the gene expression of PI3KCA isoform was higher in MM compared to normal subjects. BYL719, a novel and specific PI3KCA inhibitor inhibited the survival of primary MM cells and cell lines but not normal peripheral blood mononuclear cells. BYL719 induced the apoptosis of MM cells and inhibited their cell cycle by causing G1 arrest. BYL719 inhibited PI3K signalling, decreased proliferation and cells cycle signalling, and induced apoptosis signalling in MM cells. Finally, BYL719 synergized with bortezomib and carfilzomib, and overcame drug resistance induced by bone marrow stroma. These results were confirmed using in silico simulation of MM cell lines, BYL719 and bortezomib, and showed similar trends in survival, proliferation, apoptosis, cell signalling and synergy with drugs. In conclusion, PI3KCA plays a major role in proliferation and drug resistance of MM cells, the effects of which were inhibited with BYL719. These results provide a preclinical basis for a future clinical trial of BYL719 in MM as a single agent or in combination with other drugs.